The Newspaper as a Teaching Tool - Gustavo Garzón (Asociación Colombiana de Profesores de Ingles, 2016)
The newspaper is one of the most common information means in our society. It is an affordable way to inform oneself of current events, developments and happenings. It seeks to inform and entertain in a quick, concise and (generally) straightforward fashion. By integrating the newspaper into our language teaching, our students will greatly enhance their reading, writing, speaking and creative skills. The present paper seeks to provide the teacher with a practical way to go about this, by providing an alternate approach to newspaper use in the classroom.